Soluções para uma Classe de Equações de Schrödinger Quase Lineares via Método de Nehari - Anjos, Hudson Umbelino dos (2010)
In this dissertation, we study existence of both one-sign and nodal positive solutions (with exactly two nodal domains) for a class of quasilinear Schrödinger equations, which model physic phenomena, for example, in plasma physics. To obtain the results, it was used, mainly, the Nehari method, as well as, regularity theory of elliptic and Concentration-Compactness Principle.